Neural markers of category-based selective working memory in aging - Mok, R; O'Donoghue, C; Myers, N; Drazich, E; Nobre, A (Elsevier, 2019)
Working memory (WM) is essential for normal cognitive function, but shows marked decline in aging. The importance of selective attention in guiding WM performance is increasingly recognized. Studies so far are inconclusive about the ability to use selective attention during WM in aging. To investigate the neural mechanisms supporting selective attention in WM in aging, we tested a large group of older adults using functional magnetic resonance imaging whilst they performed a category-based (faces/houses) selective-WM task. Older adults were able to use attention to encode targets and suppress distractors to reach high levels of task performance. A subsequent, surprise recognition-memory task showed strong consequences of selective attention. Attended items in the relevant category were recognized significantly better than items in the ignored category. Neural measures also showed reliable markers of selective attention during WM. Purported control regions including the dorsolateral and inferior prefrontal and anterior cingulate cortex were reliably recruited for attention to both categories. Activation levels in category-sensitive visual cortex showed reliable modulation according to attentional demands, and positively correlated with subsequent memory measures of attention and WM span. Psychophysiological interaction analyses showed that activity in category-sensitive areas were coupled with non-sensory cortex known to be involved in cognitive control and memory processing, including regions in the prefrontal cortex and hippocampus. In summary, we found that older adults were able to recruit a network of brain regions involved in top-down attention during selective WM, and individual differences in attentional control corresponded to the degree of attention-related modulation in the brain.